Effect of Structural Differences in Naringenin, Prenylated Naringenin, and Their Derivatives on the Anti-Influenza Virus Activity and Cellular Uptake of Their Flavanones - Ryosuke Morimoto; Chiaki Matsubara; Akari Hanada; Yuta Omoe; Tokutaro Ogata; Yuji Isegawa (Pharmaceuticals, 2022)
Vaccines and antiviral drugs are widely used to treat influenza infection. However, they cannot rapidly respond to drug-resistant viruses. Therefore, new anti-influenza virus strategies are required. Naringenin is a flavonoid with potential for new antiviral strategies. In this study, we evaluated the antiviral effects of naringenin derivatives and examined the relationship between their cellular uptake and antiviral effects. Madin–Darby canine kidney (MDCK) cells were infected with the A/PR/8/34 strain and exposed to the compound-containing medium for 24 h. The amount of virus in the supernatant was calculated using focus-forming reduction assay. Antiviral activity was evaluated using IC50 and CC50 values. Cells were exposed to a constant concentration of naringenin or prenylated naringenin, and intracellular uptake and distribution were evaluated using a fluorescence microscope. Prenylated naringenin showed strong anti-influenza virus effects, and the amount of intracellular uptake was revealed by the strong intracellular fluorescence. In addition, intracellular distribution differed depending on the position of the prenyl group. The steric factor of naringenin is deeply involved in influenza A virus activity, and prenyl groups are desirable. Furthermore, the prenyl group affects cellular affinity, and the uptake mechanism differs depending on its position. These results provide important information on antiviral strategies.